Peran Bank Syariah Dalam Digitalisasi Pembayaran Berbasis Qris Pada Minimarket Pondok Al Fitrah Di Era 4.0 - Oktaviani, Lusi (IQTISADIE: Journal of Islamic Banking and Shariah Economy, 2024)
This research explores the role of Islamic banks in supporting the digitization of QRIS-based payments at the Al-Fithrah Islamic Boarding School Minimarket in the Industry 4.0 era. In the context of the transformation of the banking sector through advanced information technology, QRIS (Quick Response Code Indonesian Standard) has emerged as an efficient and secure payment method, facilitating faster and more practical non-cash transactions. This study uses a qualitative approach with interviews and documentation as data collection methods. The research results show that the implementation of QRIS in the Al-Fithrah Islamic Boarding School minimarket is effective in facilitating financial circulation and increasing operational efficiency. The use of QRIS also supports financial system transparency and provides easy access for consumers. In conclusion, digitalization through QRIS has had a positive impact on increasing minimarket performance and income, showing that Islamic banks have an important role in encouraging digital financial innovation and inclusion.